Digital micro-banking as a health and protection intervention for street-connected children and youth? Analysis from a Togolese pilot - Neil Howard (BMJ Publishing Group, 2024)
Background The SaVa pilot offered street-connected children and youth (C&Y) access to digital micro-banking services to help them save money and thus avoid the violence associated with theft at night. It further used the micro-banking service as a gateway to attract C&Y towards other health and protection services. It took place over 12 months in Lomé, Togo and involved one social worker (SW) plus volunteers running 'the bank' in a non-governmental organisation-funded drop-in centre.Methods C&Y peer researchers were trained to interview and use collective drawing with peers, which they did on a bi-monthly basis. The SW recorded information about case management, training and additional services offered. He administered a survey to C&Y at the point of entry into the project and after 1 year, asking questions about recent experiences of violence or theft. At the end of 12 months, the author conducted interviews with C&Y using the bank, C&Y researchers who used the bank, project staff and steering committee partners and child protection stakeholders. One focus group was conducted with C&Y participants, alongside limited participant observation of where C&Y sleep and work.Results Findings suggest that the intervention was successful in encouraging children to open accounts and save money, and in contributing to a reduction in theft and associated violence. The incidence of theft reduced 90%; 95% of C&Y account holders were happy with the service; 200 accounts were opened. The project supported the delivery of additional services, including counselling, school reinsertion and removal from the streets.Conclusions Analysis suggests that it is possible to offer street-connected C&Y formal financial services but that this offer has potential as a health and protection intervention, especially in combination with the provision of a safe space, dedicated SW support and add-on services.